Acute Thrombotic Occlusion of Right Coronary and Left Circumflex Coronary Arteries in a Patient with Antiphospholipid Syndrome: Successful Stent Implantation - Serdar Biceroglu; Muge Ildizli Demirbas; Mustafa Karaca; Murat Yalcin; Hasan Yilmaz (Case Reports in Medicine)
Antiphospholipid syndrome is a rare disorder. Acute myocardial infarction is uncommon among these patients. Here we report a case of a 44-year-old man with antiphospholipid syndrome admitted for acute inferior myocardial infarction. Performed coronary angiography revealed that both the right coronary and the left circumflex coronary arteries were occluded by thrombi. We successfully performed primary angioplasty and stent implantation for both of the occluded coronary arteries. In the literature, this is the first case with antiphospholipid syndrome in which primary coronary angioplasty with stent implantation was successfully performed for two coronary arteries with acute thrombotic occlusion.